Immunogenicity of a Virus-Like-Particle Vaccine Containing Multiple Antigenic Epitopes of Toxoplasma gondii Against Acute and Chronic Toxoplasmosis in Mice - Guo, Jingjing; Zhou, Aihua; Sun, Xiahui; Sha, Wenchao; Ai, Kang; Pan, Ge; Zhou, Chunxue; Zhou, Huaiyu; Cong, Hua; He, Shenyi (Frontiers in Immunology, 2019)
There is no effective protective vaccine against human toxoplasmosis. Vaccines based on virus-like particles (VLPs) have proved their great success in human health for many years, but rarely applied to against Toxoplasma gondii infection. Herein, we inserted a B cell epitope (SAG182-102 or SAG1301-320)，a CD8+ cell epitopes (HF10 or ROP7) and a CD4+ cell epitope (AS15) into the truncated HBc△(aa1-149) particle to construct four chimeric HBc VLPs (HBc△H82, HBc△H301, HBc△R82 and HBc△R301). After expressed in Escherichia coli, these chimeric HBc particles presented icosahedral morphology similar to the original VLPs and were evaluated as vaccines against acute and chronic toxoplasmosis in mouse model. The results showed that all these chimeric HBc particles induced strong humoral and cellular immune responses with high IgG antibody titer and IFN-γproduction. Only the mice immunized with HBc△H82 displayed signiﬁcantly prolonged survival time (15.6±3.8 days vs. 5.6±0.8 days) against acute infection with RH tachyzoite and reduction in brain parasite load (1454±239 vs. 2091±263) against chronic infection with Pru cyst compared to unimmunized group. These findings suggested that, as an effective carrier to deliver effective multiple antigenic epitopes, the HBc VLPs would be beneﬁcial to develop a safe and long-acting vaccine against toxoplasmosis.